Effects of school-based high-intensity interval training on health-related fitness in adolescents - Jovanović, Rade; Živković, Mladen; Stanković, Mima; Zoretić, Dajana; Trajković, Nebojša (Frontiers in Physiology, 2024)
BackgroundHigh-intensity interval training (HIIT) in school settings has been much less studied in adolescents. The aim of this study was to examine the impact of HIIT on health-related fitness in adolescents.MethodsThe total sample consisted of 60 adolescents (age 16.33 ± 0.62 years) from secondary Grammar school, randomly divided into two groups: the experimental (EG) (30) and the control group (CG) (30). The experimental program (12-weeks; 2 times per week) involved two Tabata sessions during one physical education class lasting 4 min each. Participants were tested for health-related fitness components-cardiorespiratory fitness (The Shuttle Run Test (SRT) and strength, hand grip test, standing long jump (SLJ) and counter movement jump (CMJ).ResultsBoth the EG and the CG experienced significant positive changes in SRT (meters) and VO2max values compared to baseline value (p < 0.05), however, the increase in the EG was significantly higher than that in the CG (SRT - ηp2 = 0.111; VO2max - ηp2 = 0.111, p < 0.01). The EG showed significant improvement in SRT (meters) and VO2max values compared to the CG (p < 0.01). Regarding the hand grip test results, a significant time × group interaction was found only for right hand (p < 0.01). Moreover, the improvements in SLJ and CMJ values was greater in EG than that in the CG group (SLJ- ηp2 = 0.182; CMJ- ηp2 = 0.112, p < 0.01).ConclusionFindings indicate that HIIT implemented into physical education classes can result in significant improvements in selected health related fitness components in adolescents.